Determinant Employee Performance Through Individual Characteristics, Quality of Work Life, and Work Facilities - Rizki, Via Lailatur; Muttaqien, Fauzan; Fitria, Novy; Irwanto , Jesi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
Optimal performance is often influenced complexity factors, including individual characteristics, quality of work life and work facilities which are one of the company's operational references in improving performance. Employee performance is the main focus of every company in order to achieve related goals. The case study in this research is at PT. Serbuk Jaya Abadi found in Lumajang. The purpose of study is to examine the effect of individual characteristics, quality life work and facilities work effect on performance employees. Population of this study 150 employess. This research used the Slovin method sampling and distributing questionnaires to 60 samples namely employees PT. Serbuk Jaya Abadi obtained from sampling method. The analysis method in this research uses analysis multiple linear regression with results, individual characteristics do not has a significant effect on performance, quality of work life has a significant effect on performance, work facilities has a significant effect on performance.